Pengembangan Aplikasi Traffic Light E-Tilang Menggunakan Google Geofencing API Berbasis Android - Ditya Enandini Palupi; Muhammad Aminul Akbar; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The level of traffic violations in Indonesia is increasing. This is evidenced by the increasing number of accidents in the city of Surabaya. In order to reduce the reduction of road traffic violations, it is necessary to have rules or guidance to the public for the importance of obeying the traffic rules set by the government. Surabaya Transportation Department is one of institutions or agencies that provide infrastructure and transportation facilities to support local development activities and improve the welfare of the community, one of them by facilitating CCTV cameras. The camera is enabled to implement an electronic ticketing system that operates since the beginning of September 2017. With the help of CCTV, the system can help identify the types of violations, offenders, to where the offense is located. The authors conducted a survey to 30 respondents tekait necessary needs for vehicle users who do not know when and where the conduct of the offense. Against this background, a traffic light monitoring system application was created to make it easier for vehicle users to locate infringement information and give users a warning that enters the traffic light area. Implementation is done with Android Studio. Testing is done by passing an area and the result of distance based on vehicle speed.